2023
DOI: 10.3389/fmed.2023.1132574
|View full text |Cite
|
Sign up to set email alerts
|

Perifolliculitis capitis abscedens et suffodiens treatment with tumor necrosis factor inhibitors and baricitinib: A case report and literature review

Abstract: RationalePerifolliculitis capitis abscedens et suffodiens (PCAS), also known as dissecting cellulitis of the scalp (DCS), is a part of the “follicular occlusion tetrad” that also includes acne conglobate (AC), hidradenitis suppurativa (HS), and pilonidal sinus, which share the same pathogenic mechanism, such as follicular occlusions, follicular ruptures, and follicular infections.Patient concernsA 15-year-old boy had multiple rashes on the scalp accompanied by pain.DiagnosisThe patient was diagnosed with PCAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Features of DCS overlap with many core qualities of HS, such as the type of lesions present, recurrence of lesions, and its suppurative nature, with the main difference being the location of the disease. These two diseases often coexist [ 1 ]. Oral JAK1 inhibitors have shown preliminary efficacy in treating moderate-to-severe HS in two phase II studies, have demonstrated high clinical responses in cohort studies, and are currently undergoing a phase III trial for HS [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Features of DCS overlap with many core qualities of HS, such as the type of lesions present, recurrence of lesions, and its suppurative nature, with the main difference being the location of the disease. These two diseases often coexist [ 1 ]. Oral JAK1 inhibitors have shown preliminary efficacy in treating moderate-to-severe HS in two phase II studies, have demonstrated high clinical responses in cohort studies, and are currently undergoing a phase III trial for HS [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent case studies, tumor necrosis factor-alpha inhibitors have shown some promise in DCS refractory to conventional treatment, a therapy also indicated for moderate-to-severe HS [ 10 , 11 ]. One recent case of an adolescent with DCS demonstrated a successful response to treatment with adalimumab and baricitinib [ 1 ]. However, there is no literature detailing the use of JAK inhibitors as a potential therapy for DCS, and to our current knowledge, this is the first case of recalcitrant DCS successfully responding to a trial of upadacitinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations